Plateau Lake Water Quality and Eutrophication: Status and Challenges - Zhang, Hucai; Chen, Jingan; Haffner, G.D (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The continuous and widespread deterioration of lake water quality and eutrophication is not only a local problem, but also a global phenomenon. It is not only destroying, or at least limiting, the valuable water resources for daily life, but threatening the water security of sustainable social development. More importantly, along with the rapid accumulation of the alga, including novel hypertoxic viruses and new toxic chemicals, as well as other organic compounds, these stressors threaten aquatic life, biodiversity and endanger our health.This Special Issue highlights and discusses major threats to Plateau Lakes water quality, and provides an update on both lake current status, as well as future challenges. Lake problems, such as pollution and eutrophication, require that we quantify how serious the situation is, identify the probable causes, and recommend how to control the pollution in order to restore and protect water quality. More importantly, this Special Issue stresses the need to manage the lakes and the watershed under a unified approach.